Public attitudes toward immigration policies in South Korea. Issue 2 (4th May 2019) - Chang, Han Il
ABSTRACT: This paper examines whether economic or socio-psychological concerns determine anti-immigration attitudes in South Korea, in an effort to address regional asymmetries in existing immigration studies. An analysis reveals that labour market competition and fiscal burden concerns do not affect anti-immigration attitudes, but xenophobia, the conceptual views of citizenship, and the expectation of the impact of immigration on the national economy determine anti-immigration attitudes, a result in keeping with existing studies of anti-immigration attitudes in European or North American countries. However, when policies have humanitarian dimensions, the ethno-cultural views of Korean identity tend to reduce anti-immigration attitudes, a finding that runs counter to the empirical results from studies in the Western context. In addition, multiculturalism appears to affect anti-immigration attitudes when measured in terms of general immigration policies, but not when specific immigration groups are referenced. I conclude by discussing the implications of these new findings.